Preaching water but drinking wine? Relative performance evaluation in international banking - Dragan Ilić; Sonja Pisarov; Peter S. Schmidt (Swiss Journal of Economics and Statistics, 2019)
The rise in the level of executive compensation in international banking in the last two decades has been striking. At the same time, corporate declarations of relative performance evaluation (RPE) have enjoyed widespread popularity. RPE determines the level of CEO pay by accounting for common market shocks that are out of a CEO's control, providing better governance and incentivizing CEOs to maximize shareholder value. In this paper, we test for evidence of RPE in international banking and pay particular attention to banks that openly disclose its use. To that end, we collect compensation data on 46 large international banks. Taken as a whole, our sample shows moderate evidence consistent with RPE. We report stronger evidence once we investigate the subsample of RPE-disclosing banks. These results hold up to a series of robustness checks. In addition, we find that the use of RPE is positively related to firm size and negatively related to growth options.
Keywords: D86; G21; G3; J33; 330; Relative performance evaluation; Executive compensation; Peer group; Banks; Disclosure